The Role of Innovation in Startup Success: A Comprehensive Review - Kartika, Fina (Advances: Jurnal Ekonomi & Bisnis, 2024)
This structured abstract provides a comprehensive review of the role of innovation in startup success. The purpose of this study is to examine the significance of innovation in the success of startup businesses. The study design/methodology/approach involves a systematic review of existing literature, including academic articles, books, and reports, to gather relevant information on the topic. The findings of this review indicate that innovation plays a critical role in the success of startups, as it enables them to differentiate themselves in competitive markets, create unique value propositions, and adapt to changing market conditions. Additionally, innovative startups are more likely to attract investment, build strong customer relationships, and achieve sustainable growth. The originality of this review lies in its comprehensive examination of the role of innovation in startup success, highlighting its multifaceted impact on various aspects of a business's performance. This review contributes to the existing body of knowledge by consolidating key findings and providing a holistic understanding of the significance of innovation for startups. It offers insights and implications for startup founders, investors, policymakers, and researchers, emphasizing the imperative of fostering a culture of innovation to enhance startup success and drive economic growth.